Becoming home diaspora and the Anglophone transnational - Nixon, Jude V. 1953-; Constantini, Mariaconcetta (Series in literary studies, 2022)
"Becoming Home: Diaspora and the Anglophone Transnational” is a collection of essays exploring national identity, migration, exile, colonialism, postcolonialism, slavery, race, and gender in the literature of the Anglophone world. The volume focuses on the dispersion or scattering of people in exile, and how those with an existing homeland and those displaced, without a politically recognized sovereign state, negotiate displacement and the experience of living at home-abroad. This group includes expatriate minority communities existing uneasily and nostalgically on the margins of their host country.